Studi Teologis Makna Menghujat Roh Kudus Menurut Injil Sinoptik Sebagai Dosa Yang Tidak Diampuni - Paulus Kunto Baskoro; Samuel Purdaryanto (Manna Rafflesia, 2022)
Sin is an attitude that destroys human life (Ps. 32: 3-4; 51: 4, 7). Since the fall of the first man in the garden of Eden, all humans have been under the bondage of sin (Gen. 3; Rom. 5:12-14). Over time, all attempts at repair fail and one error leads to another (Isa. 64:6; Rom. 3:10-12). Various issues regarding the sin of blaspheming the Holy Spirit as an unpardonable sin have caused anxiety in the hearts of believers because they think they have committed the sin without realizing it. This study uses the descriptive method of literature as the method used to describe or present the results based on a literature review as well as by extracting hermeneutics and exegesis of texts in the synoptic gospels. The purpose of this study is, first, to describe the notion of blaspheming the Holy Spirit as an unpardonable sin, using appropriate and biblical principles. Second, compare the results of the interpretation with several interpretations that contrast with the statements of the Bible in other parts that take all sin seriously (Rom. 6:23). Third, every believer has a complete understanding of the meanings of sin, so that they can seriously live in Christ.